Personal and demographic determinants of disaster preparedness in the first District in Zamboanga del Norte - Pangilinan, Ninfa B. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2015)
This study was conducted to determine the personal and demographic determinants of disaster preparedness in the first district of Zamboanga del Norte. Finding revealed that earthquake, tropical cyclone, flood and thunderstorm were dominantly experienced by the respondents for the past five years. Young and old residents, educated and less educated, employed and not employed, poor and not poor, married and not married, resided in a place longer or living in an insured and not insured houses were found not significant determinants of disaster preparedness. However, males and females significantly determined disaster preparedness where females were assumed to be often vulnerable to hazards because of their role-related responsibilities and more – risk averse than the males. Hence, paying careful regard to proposing disaster preparedness plan should be formulated which includes activities and measures to be taken in advance to ensure effective response to the impact of hazards.